Genetic risk-dependent brain markers of resilience to childhood Trauma - Lu, Han; Rolls, Edmund T.; Liu, Hanjia; Stein, Dan J.; Sahakian, Barbara J.; Elliott, Rebecca; Jia, Tianye; Xie, Chao; Xiang, Shitong; Wang, Nan; Banaschewski, Tobias; Bokde, Arun L. W.; et al. (Nature Communications, 2025)
Resilience to developing emotional disorders is critical for adolescent mental health, especially following childhood trauma. Yet, brain markers of resilience remain poorly understood. By analyzing brain responses to angry faces in a large-scale longitudinal adolescent cohort (IMAGEN), we identified two functional networks located in the orbitofrontal and occipital regions. In girls with high genetic risks for depression, higher orbitofrontal-related network activation was associated with a reduced impact of childhood trauma on emotional symptoms at age 19, whereas in those with low genetic risks, lower occipital-related network activation had a similar association. These findings reveal genetic risk-dependent brain markers of resilience (GRBMR). Longitudinally, the orbitofrontal-related GRBMR predicted subsequent emotional disorders in late adolescence, which were generalizable to an independent prospective cohort (ABCD). These findings demonstrate that high polygenic depression risk relates to activations in the orbitofrontal network and to resilience, with implications for biomarkers and treatment.